2021
DOI: 10.1016/j.tourman.2020.104169
|View full text |Cite
|
Sign up to set email alerts
|

Mental health key to tourism infrastructure in China's new megapark

Abstract: The global economic value of parks through improved mental health of tourists has been estimated at about ten times greater than direct park tourism expenditure. The Chinese term for this health services value is jing hua xin ling , psychological destressing. Here we present the first case where optimal tourist infrastructure is influenced by including mental health. Using a multi-stage, cross-lingual, differential stakeholder method, we analyse conflicts between road- and roadless-acces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 98 publications
1
39
0
1
Order By: Relevance
“…Stakeholder relationships come from issues that are critical to creating and distributing value [109]. A study in China analyzed the conflicts between road-and roadless-access tourism in China's large new national park, and a differential tourism stakeholder analysis was conducted [110]. A study in Taichung, Taiwan that used social exchange and stakeholder theory investigated the effect of residents' perceived benefits and costs on the subjective well-being and support of megaevents [111].…”
Section: Tourism Stakeholders and The Covid-19 Pandemicmentioning
confidence: 99%
“…Stakeholder relationships come from issues that are critical to creating and distributing value [109]. A study in China analyzed the conflicts between road-and roadless-access tourism in China's large new national park, and a differential tourism stakeholder analysis was conducted [110]. A study in Taichung, Taiwan that used social exchange and stakeholder theory investigated the effect of residents' perceived benefits and costs on the subjective well-being and support of megaevents [111].…”
Section: Tourism Stakeholders and The Covid-19 Pandemicmentioning
confidence: 99%
“…Support domestic and regional tourism Adopt tax reduction measures for domestic tourism; provide digital coupons to support tourism; reduce dependence on long-distance tourists and support regional and VFR (visiting friends and relatives) tourism [18,22,23] Restore market confidence Use big data to investigate the perception of tourists; ensure the safety of destination travel [22,24,25] Carry out intergovernmental cooperation Establish common standards and sanitation agreements between governments, and set up international safe tourism border areas [21,26] Redefine community-based tourism Redefine and reposition the tourism industry according to the rights and interests of local people; ensure the participation of indigenous people and protect their right to know; incorporate indigenous values into national tourism policy planning [18,27]…”
Section: Measures Example Sourcementioning
confidence: 99%
“…Under this theme, on the one hand, many scholars have conducted surveys on tourists' current reactions to travel under COVID-19 and found that the negative impact of COVID-19 has significantly affected the health risks perceived by tourists (for example, [25,[28][29][30]). As a result, tourists' avoidance of travel during the health crisis is caused.…”
Section: Tourist Perception and Decision-makingmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, interest has grown in the positive benefits that might be gained from natural environments and time spent outdoors [23][24][25]. Nature exposure, including park playing, bird watching, and sporting activities in natural environments can keep people mentally active and healthy [26][27][28]. However, restrictions on the use of public green spaces, quarantine, and social distancing as effective measures implemented to tackle the COVID-19 and protect public health during the pandemic.…”
Section: Introductionmentioning
confidence: 99%